Prospects for using gamification in Industry 4.0 - Ana Carla Bittencourt Reis; Everaldo Silva Júnior; Brenda Baumann Gewehr; Mateus Halbe Torres (Production)
Abstract Paper aims This study aims to analyze the main applications of gamification in the industry, identifying its benefits and challenges, and to understand how game techniques are impacting the formation of engineers. Finally, the main perspectives of the use of gamification in the Industry 4.0 are presented. Originality The scientific literature was analyzed to infer practical applications, challenges, benefits and perspectives that can guide the implementation of gamification in Industry 4.0, aiming to help professionals and researchers to take better advantage of this approach and propel this new phase of the industry. Research method A literature review was conducted on the use of gamification in the industry. Main findings In this article, eleven aspects that must be taken into consideration during the application of gamification in the industries were observed. Five perspectives/situations of Gamification use were raised, namely: in the servitization; in learning and training; as a tool to increase intrinsic motivation; introducing new technologies and products; and innovation and flexibility. Implications for theory and practice This study systematically brings together the main approaches to gamification and its applications in the current industry scenario. In addition, this work contributes to the process of designing and implementing gamification in the industry.